Non-technical skills learning in healthcare through simulation education: integrating the SECTORS learning model and complexity theory. (20th August 2015) - Gordon, Morris; Box, Helen; Farrell, Michael; Stewrt, Alison
Abstract : Recent works have reported the SECTORS model for non-technical skills learning in healthcare. The TINSELS programme applied this model, together with complexity theory, to guide the design and piloting of a non-technical skills based simulation training programme in the context of medicines safety. The SECTORS model defined learning outcomes. Complexity Theory led to a simulation intervention that employed authentic multi-professional learner teams, included planned and unplanned disturbances from the norm and used a staged debrief to encourage peer observation and learning. Assessment videos of non-technical skills in each learning outcome were produced and viewed as part of a Non-Technical Skills Observation Test (NOTSOT) both preintervention and postintervention. Learner observations were assessed by two researchers and statistical difference investigated using a student's t test. The resultant intervention is described and available from the authors. Eighteen participants were recruited from a range of inter-professional groups and were split into two cohorts. There was a statistically significant improvement (p=0.0314) between the Mean (SD) scores for the NOTSOT pre course 13.9 (2.32) and postcourse 16.42 (3.45). An original, theoretically underpinned, multiprofessional, simulation based training programme has been produced by the integration of the SECTORS model for non-technical skills learning the complexity theory. This pilot work suggests the resultant intervention can enhance non-technical skills.